(untitled) (Impetus, 2021)
To analyze the healthy lifestyles that a group of students from the Pontificia Universidad Javeriana exhibits before and after taking the elective sports subject Cardio-Conditioning. It is developed under the paradigms of the quantitative approach and a sequential, deductive and probative process, which does not allow any phase of the methodological design to be eluded. As it is a study carried out on 62 specific students from the Javeriana University, particularly from the sports elective subject Cardio-conditioning, who are given an analysis of changes in behavior compared to what has to do with lifestyle, it is considered that the research has a longitudinal descriptive scope of group evolution. According to investigations of this type, they are characterized by making use of data collection techniques focused on the validation of hypotheses, based on the measurement of numerical information and analysis. The data obtained and the findings found show that the total of the selected sample that attend the sports elective Cardio-Conditioning belongs to the male gender, which may be an indication that there is greater interest. 17.7% have been developing an acceptable routine to achieve or, failing that, improve their lifestyle and preserve their health. However, the majority of the group studied, according to preliminary findings, indicates that their habits allow them to have a healthy lifestyle.